2017
DOI: 10.1111/ivb.12173
|View full text |Cite
|
Sign up to set email alerts
|

Life history traits and previous exposure predict resistance to UV irradiation in the freshwater cnidarian Hydra oligactis

Abstract: Abiotic stress is an important source of mortality for cnidarians and is likely to be a major factor shaping their life histories. In freshwater hydra, the ability to withstand exogenous sources of stress varies between species and populations, but little is known about the factors responsible for this variation. Here, we investigated resistance to UV irradiation in Hydra oligactis, a common temperate freshwater cnidarian. We collected polyps from 12 populations and propagated these asexually under standard co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 64 publications
(111 reference statements)
0
5
1
Order By: Relevance
“…H. oligactis resembles cyclical parthenogenetic cladocerans in that it switches to a sexual mode of reproduction under conditions favouring dormancy (Tessier & Caceres, 2004). Although previous studies have suggested that there may be some genetic differences between different genotypes in this species (Tökölyi, Kozma, et al, 2017; Tomczyk et al, 2015), such a difference was not observed in this study. Hydra individuals engaged in each reproductive strategy are phenotypically very different, but we did not find significant genetic differentiation between sexual and asexual polyps.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…H. oligactis resembles cyclical parthenogenetic cladocerans in that it switches to a sexual mode of reproduction under conditions favouring dormancy (Tessier & Caceres, 2004). Although previous studies have suggested that there may be some genetic differences between different genotypes in this species (Tökölyi, Kozma, et al, 2017; Tomczyk et al, 2015), such a difference was not observed in this study. Hydra individuals engaged in each reproductive strategy are phenotypically very different, but we did not find significant genetic differentiation between sexual and asexual polyps.…”
Section: Discussioncontrasting
confidence: 77%
“…This suggests that there are some internal factors or environmental cues other than temperature that might induce sexual reproduction in this species. First, variation in individual condition due to differences in the availability and predictability of food, population density, age, size or previous exposure to stressors and parasites are factors with a known effect on life history traits in this species (Tökölyi et al, 2016; Tökölyi, Kozma, et al, 2017; Tökölyi, Kozma, et al, 2017). Second, particular microhabitats might occur in the examined water bodies, which could provide favourable conditions for Hydra polyps with either sexual or asexual reproduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the results presented in this study, polyp age could be one of the factors determining this plasticity, such that younger polyps reproduce asexually, while older ones initiate sexual reproduction when temperature drops during autumn. In addition to age, external factors such as food availability (Tökölyi, Kozma, Sebestyén, Miklós, & Barta, 2017) or population density (Bell & Wolfe, 1985) might contribute to variation in reproductive strategies, but the relative role of these factors remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, to see whether differences in sexual readiness between seasons is due to 120 phenotypic plasticity, as predicted by our hypothesis, we performed warm exposure experiments in two 121 lab strains (one male and one female) and looked at changes in sexual readiness in response to 122 exposure to elevated temperature. Hydra (Tökölyi et al 2017a, 2017b, Sebestyén et al 2018. The asexual propagation phase lasted for 10 weeks.…”
mentioning
confidence: 99%